Getting clocked: screening for TBI-related cognitive impairment with the clock drawing test. (19th September 2017) - Hazan, Elias; Zhang, Jia; Brenkel, Megan; Shulman, Kenneth; Feinstein, Anthony
ABSTRACT: Primary Objective: Undetected cognitive impairment resulting from Traumatic Brain Injuries (TBIs), particularly the 75–95% classified as mild (mTBI), poses a significant public health challenge as untreated symptoms, can persist and cause lasting disability. These cognitive deficits are often missed by standard screening tests, creating a need for alternative cognitive screening tools. The Clock Drawing Test (CDT), a popular, brief cognitive screening instrument, was used to evaluate cognition in persons with TBI. Design: The effectiveness of the CDT was assessed on its own and in tandem with a validated computerised screening battery, including the Stroop Test, Symbol Digit Modalities Test (SDMT), and Paced Visual Serial Addition Test 2-second trials (PVSAT-2). Methods and Procedures: The clock drawing component of the Montreal Cognitive Assessment (MoCA) of 223 subjects attending an outpatient TBI clinic was scored using two different methods. Main Outcomes and Results: The CDT screened for cognitive impairment most effectively when scored using the Clock Drawing Interpretation Scale (CDIS). Cognitive impairment was detected in 19.4% of the elusive cohort of persons with mTBI. Conclusions: The results of this study suggest that the CDT is effective at screening for cognitive impairment in persons with TBI. The CDT could be a valuable supplementary tool in TBI clinics as well as an effective cognitive screening instrument in busy primary care settings.